Customized 3D-Printed Mesh, Membrane, Bone Substitute, and Dental Implant Applied to Guided Bone Regeneration in Oral Implantology: A Narrative Review - Federica Di Spirito; Francesco Giordano; Maria Pia Di Palo; Cosimo Ferraro; Luigi Cecere; Eugenio Frucci; Mario Caggiano; Roberto Lo Giudice (Dentistry Journal)
Background: The new frontiers of computer-based surgery, technology, and material advances, have allowed for customized 3D printed manufacturing to become widespread in guided bone regeneration (GBR) in oral implantology. The shape, structural, mechanical, and biological manufacturing characteristics achieved through 3D printing technologies allow for the customization of implant-prosthetic rehabilitations and GBR procedures according to patient-specific needs, reducing complications and surgery time. Therefore, the present narrative review aims to elucidate the 3D-printing digital radiographic process, materials, indications, 3D printed manufacturing-controlled characteristics, histological findings, complications, patient-reported outcomes, and short- and long-term clinical considerations of customized 3D printed mesh, membranes, bone substitutes, and dental implants applied to GBR in oral implantology. Methods: An electronic search was performed through MEDLINE/PubMed, Scopus, BioMed Central, and Web of Science until 30 June 2024. Results: Three-dimensionally printed titanium meshes and bone substitutes registered successful outcomes in vertical/horizontal bone defect regeneration. Three-dimensionally printed polymeric membranes could link the advantages of conventional resorbable and non-resorbable membranes. Few data on customized 3D printed dental implants and abutments are available, but in vitro and animal studies have shown new promising designs that could improve their mechanical properties and tribocorrosion-associated complications. Conclusions: While 3D printing technology has demonstrated potential in GBR, additional human studies are needed to evaluate the short- and long-term follow-up of peri-implant bone levels and volumes following prosthetic functional loading.